The Acceptance of COVID-19 Vaccination Under Different Methods of Investigation: Based on Online and On-Site Surveys in China - Yun Lyu; Yun Lyu; Xiaozhen Lai; Xiaozhen Lai; Xiaochen Ma; Lei Cao; Hong Lei; Jiahao Wang; Jiahao Wang; Haijun Zhang; Haijun Zhang; Rize Jing; et al. (Frontiers in Public Health, 2021)
As Coronavirus Disease-2019 (COVID-19) vaccines became available in December 2020, increasingly more surveys were organized to examine the acceptance of vaccination, while most of them were conducted online. This study aimed to explore the difference between online and traditional on-site surveys in terms of COVID-19 vaccine acceptance. From November to December 2020, an online survey (n = 2013) and an on-site survey (n = 4,316) were conducted simultaneously in China. Multivariate logistic regression was used to identify influencing factors of acceptance, and propensity score matching (PSM) was adopted to balance the outcomes. As a result, 90.0% of the online respondents accepted COVID-19 vaccination, while it was only 82.1% in the on-site survey. After applying PSM, the acceptance rate of the on-site survey was declined to 78.6%. The age structure, residence location, education, and health status were observed as important factors in addressing vaccination acceptance, which needed to be specifically considered when designing online surveys.